Evaluation the Occurrence of Human Cytomegalovirus (HCMV) and its Relation to Some Biochemical Markers in Hemodialysis Patients from Kirkuk City/Iraq - Abdulla, Abdulla Kamil (American Journal of Bioscience and Clinical Integrity, 2025)
Background and Objectives: Across all socioeconomic categories, Cytomegalovirus (CMV) is extremely common worldwide and affects 50.0% to 85.0% of persons over 40. Most of its infections are asymptomatic in children and are typically prevalent in the community. The seroprevalence of CMV varies between 40 and 60 percent in Africa and 80 and 100 percent in Latin America, respectively, and between 65 and 85 percent in Brazil. Cytomegalovirus (CMV) infection is one of the main causes of death for individuals receiving hemodialysis (HD). Aim: To evaluate prevalence of anti-HCMV antibodies among Hemodialysis patients and their correlation with some biochemical parameters. Materials and Methods: The present study (case-control study), was achieved at the Hemodialysis department of Kirkuk General Hospital, Kirkuk city, Iraq, during the period of first of July 2024 to 15 of June 2025. The participants included 128 patients (70 male and 58 female) who have had Hemodialysis and aged (40-80) years old and 93 individuals who used as control group (60 male and 33 female) who their ages were close to age groups of the patients. Some immunological and biochemical parameters had measured for the participants. Results: It was documented that the highest rate, 22 (31.42%), was found in male patients aged (56–65) years, while the lowest proportion, 1 (1.72%), was found in female patients aged 25–35 years. Likewise the present study showed significant lowering of the mean concentration levels of vitamin D3 (15.32±6.41 ng/mL) among the hemodialysis patients in comparison to (27.40±8.80 ng/mL) recorded for the control group. Concerning the Serum Creatinine and B. Urea mean levels, they recorded extremely significant variances (P<0.0001), between the patients and controls. For those patients who have both (IgM +, and IgG +) displayed 51 (39.84%), while the control group showed 8(8.60%). Conclusion: Old men who are on Hemodialysis are more susceptible to get reactivated HCMV. Low Vitamin D3, and S. Albumin could increase the severity of the infection. Patients on Hemodialysis could get reactivation with HCMV easily.